(untitled) (Memorias Sifored - Encuentros Educación UAN, 2022)
Recently, education and technology have become an intersection with multiple variables, which allow us to reflect especially on the tensions caused by the COVID-19 pandemic, therefore, in academic spheres and specifically those concerning education, this convergence is recognized, as well as the importance of constantly updating pedagogical processes with the needs that arise in a globalized world. Consequently, different pedagogical proposals have emerged, crossed by virtual spaces that are essential to rethink the university, allowing for different ways of being in the world. The digital scenario can be analyzed in terms of education and pedagogy from different angles, making subjectivities more complex from the intersections that can occur between: sexuality, gender, digital citizenships and algorithms. The methodology used to obtain the information and its subsequent reflection, was the Bibliographic Research, which collected a series of documents, which were organized and categorized according to their information to later carry out a rigorous analysis of them and determine the benefit of their application. The digital world is a network of connections that converge in the same place and it is essential that pedagogy be a measure of the relationships that are woven there. It is important from perspectives such as queer within education, to promote a free and harmonious stay in digital settings, as well as the understanding of categories from digital spaces that allow access to their knowledge.